Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-long.226
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Cross-Lingual Sentence Representation Learning

Abstract: Large-scale models for learning fixeddimensional cross-lingual sentence representations like LASER (Artetxe and Schwenk, 2019b) lead to significant improvement in performance on downstream tasks. However, further increases and modifications based on such large-scale models are usually impractical due to memory limitations. In this work, we introduce a lightweight dual-transformer architecture with just 2 layers for generating memory-efficient cross-lingual sentence representations. We explore different trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, manually cleaned high-quality ground-truth bilingual dictionaries are used to pre-edit the source sentences, which are unavailable for most language pairs. Recently, contrastive objectives (Clark et al, 2020;Gunel et al, 2021;Giorgi et al, 2021;Wei et al, 2021;Mao et al, 2021) have been shown to be superior at leveraging alignment knowledge in various NLP tasks by contrasting the representations of positive and negative samples in a discriminative manner. This objective, which should be able to utilize word alignment learned by any toolkit, which in turn will remove the constraints of using manually constructed dictionaries, has not been explored in the context of leveraging word alignment for many-to-many NMT.…”
Section: Introductionmentioning
confidence: 99%
“…However, manually cleaned high-quality ground-truth bilingual dictionaries are used to pre-edit the source sentences, which are unavailable for most language pairs. Recently, contrastive objectives (Clark et al, 2020;Gunel et al, 2021;Giorgi et al, 2021;Wei et al, 2021;Mao et al, 2021) have been shown to be superior at leveraging alignment knowledge in various NLP tasks by contrasting the representations of positive and negative samples in a discriminative manner. This objective, which should be able to utilize word alignment learned by any toolkit, which in turn will remove the constraints of using manually constructed dictionaries, has not been explored in the context of leveraging word alignment for many-to-many NMT.…”
Section: Introductionmentioning
confidence: 99%